Penanaman Karakter Kreatif Melalui Pembiasaan Kuliah Tujuh Menit - Putri, Dela Ariyantri; Sapriya, Sapriya; Komalasari, Kokom (CIVICS: Jurnal Pendidikan Pancasila dan Kewarganegaraan, 2025)
This study aims to determine how the habit of seven-minute lectures has an impact on the instilling of creative character in students at MA Ghoyatul Jihad. The research method is descriptive. The subjects of this study were the vice principal for student affairs, teachers, and students of MA Ghoyatul Jihad. Data collection techniques used were observation, interviews, and documentation. The results of this study indicate that the habit of seven-minute lectures has an impact on the instilling of creative character in students. MA Ghoyatul Jihad has a plan in the habit of seven-minute lectures in instilling creative character, one of which is the habit carried out in stages: 1) Schedule distribution 2) Making seven-minute lecture texts 3) Implementation of seven-minute lectures 4) Student evaluation. In each stage is a process of instilling, this is what will make the creative character of students embedded. The researcher's suggestion for the school is to establish cooperation between all parties within the school environment.